Cry 1F and Cry 2Ab2 proteins survey in maize landraces and teosinte cultivated in Alto Jequitinhonha region - Rossini, Laize Cristina; Von dos Santos Veloso, Ronnie; Rodrigues Oliveira, Josimar; Alvarenga Soares, Marcus; da Costa, Márcia Regina; Siqueira da Silva, Ricardo (Revista Ceres, 2024)
Maize landraces diversity is important for many smallholder and indigenous populations. Gene flow constitutes a threat to the genetic conservation of several locally adapted maize landraces and, risk management depends on monitoring transgenic occurrence in non-GM maize. This study evaluated the occurrence of exogenous proteins from GM-maize in maize landraces and teosinte cultivated in the Alto Jequitinhonha region, State of Minas Gerais. Gene flow from GM maize to non-transgenic varieties was evaluated in eight maize groups and one teosinte variety. A transgenic maize variety was used as a positive control. Proteins Cry1F and Cry2Ab2 were monitored using the Protein Detection Assay kit (Envirologix QuickStix® kit protocols for detecting Cry1F and Cry2Ab2 proteins). Transgenic proteins were not detected in the leaves of landraces and teosinte cultivated in the Alto Jequitinhonha region.